Human anatomy from the Islamic perspectives - Yusof, Nurul Asyiqin; Che Mohamad, Che Anuar; Hassan, Ahmad Nizam; Abd. Rahman, Akmal Khuzairy (IIUM Press, International Islamic University Malaysia, 2019)
This book is designed to be a quick revision on the normal anatomy of various systems namely the cardiovascular, respiratory, musculoskeletal, gastrointestinal, reproductive, nervous and urinary. Each of the system is discussed in their own chapter. Although not exhaustive, the authors have attempted to extract as many quranic verses and hadith from Prophet Muhammad s.a.w. that relate to each system. In addition, each chapter is presented with contributions from early Muslim physicians and surgeons on the clinical-related knowledge and techniques during the early era. It is hoped that this book could be one of the sources for the integration of science and revealed knowledge for future references.